Caracterização de sedimento em áreas rurais e urbanas do município de Toledo-PR - Juchen, Carlos Roberto (2014)
The present study aims to determine trace elements concentration, adsorbed by sediments in waterproofed areas of the city limits as well as sediments that are deposited in the main rivers beds, which are responsible to perform drainage in Toledo city, Paraná. In order to study the sediment enrichment by trace elements, initially, there was some need to know the basal contents of these elements at the researched site. Therefore, and according to the scientific guidelines for this procedure, the chosen soil samples were taken from legal reserve areas located in the nearby rural farms, since these areas meet the requirements of preserving the natural characteristics of the soil in this region. Thus, five (5) sites were selected for sampling sediments on the streets as well as five (5) sites from the main rivers that have received sediments carried from the urban area by natural and anthropogenic processes. There were monthly collections in the studied rivers from April 2012 to March 2013 as well as fortnightly monitoring concerning the main physical parameters of river water (pH, dissolved oxygen, oxide reduction potential, conductivity, total dissolved solids, temperature and turbidity) in order to determine how these conditions can interfere on trace elements adsorbed by sediments deposited in the water environment. The applied analytical techniques were inductively coupled argon plasma-atomic emission spectroscopy (ICP-OES), total organic carbon (COT), laser granulometry and mineralogy by diffraction. The background showed the following concentrations: Fe (105,956), Al (102,372) Mg (2,303.2), Mn (916.4), Na (493.1), Cu (212.3), Zn (82.14 ), Ba (62.51), Cr (52.4), Ni (30.36), Pb (17.46), Sb (4.58) and Cd (0.69) in mg kg-1. The statistical analysis of the main components is summarized in three components that explained 96% variability of the background results, thus, it shows that there is no source of geogenic or anthropogenic contamination on the legal reserves. The sediments were classified as having an average particle size greater than 0.09 mm. The average clay fraction varied from 2 to 6% of the total mass of sediment samples. Mineralogical presences in the urban and aquatic environments were equivalent; they presented the following decreasing sequence number of the following minerals: quartz> hematite> andesite> kaolinite. They were compared to the background levels previously determined, the sediments of streets and rivers were enriched by trace elements in the following percentage rates: Ba (45.4 to 39.3%), Cu (48.6 to 44.3%), Cr (37.2 to 56.3%), Mn (81.6 - 0%), Ni (0 - 18.6%), Pb (40 - 0%), Zn (283.7 to 140.2 %), Mg (34.3 to 18.4%) and Na (250.2 to 295%), while TOC percentages showed an average distribution of 1% in all sites where samples were analyzed. The highest geo-accumulation rates were obtained where there was great enrichment by Zn as a trace element and according to the main guidelines, the maximum values obtained by trace elements such as Cd, Cr, Cu, Ni and Zn can produce adverse effects in this watershed. Finally, the monitoring methodology using control charts associated with the scores of the main components has demonstrated that among the monitored physicochemical parameters, electrical conductivity was retained in all the first components of the analyzed rivers. Thus, this parameter showed the highest correlations that interfere in the processes of adsorption and desorption of trace elements from sediments to water environment. At last, it was concluded that rural and urban anthropogenic contributions are responsible for the enrichment of sediments by trace elements in this area of study and also that scientific data are important for future environmental management processes of this municipality.